ISLPED'06 Proceedings of the 2006 International Symposium on Low Power Electronics and Design 2006
DOI: 10.1109/lpe.2006.4271802
|View full text |Cite
|
Sign up to set email alerts
|

Energy/Power Breakdown of Pipelined Nanometer Caches (90nm/65nm/45nm/32nm)

Abstract: As transistors continue to scale down into the nanometer regime, device leakage currents are becoming the dominant cause of power dissipation in nanometer caches, making it essential to model these leakage effects properly. Moreover, typical microprocessor caches are pipelined to keep up with the speed of the processor, and the effects ofpipelining overhead need to be properly accounted for.In this paper, we present a detailed study of pipelined nanometer caches with detailed energy/power dissipation breakdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…6 Also, with each CMOS technology generation, leakage power has been dramatically increasing. 7 Hence, large LLCs spend a signi¯cant fraction of their energy in the form of leakage energy. Our experiments using 32-nm technology node have shown that for single-core and dualcore con¯gurations, the leakage energy of L2 cache is more than 95% of the total L2 cache energy c (dynamic energy þ leakage energy).…”
Section: Introductionmentioning
confidence: 99%
“…6 Also, with each CMOS technology generation, leakage power has been dramatically increasing. 7 Hence, large LLCs spend a signi¯cant fraction of their energy in the form of leakage energy. Our experiments using 32-nm technology node have shown that for single-core and dualcore con¯gurations, the leakage energy of L2 cache is more than 95% of the total L2 cache energy c (dynamic energy þ leakage energy).…”
Section: Introductionmentioning
confidence: 99%
“…As the number of inactive (idle) transistors begins to dominate the number of active transistors [3], static energy becomes the major source of energy consumption. In order to have a thorough understanding of memory system behavior, we need to accurately account for both static and dynamic components of energy in the presence of spatio-temporal variations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to have a thorough understanding of memory system behavior, we need to accurately account for both static and dynamic components of energy in the presence of spatio-temporal variations. Energy estimation in caches is possible through analytical, empirical and a combination of both methods [3,4,5,6,7]. Analytical models require a deep understanding of device-level physics while empirical models replicate the behavior of results produced by experiments on actual systems.…”
Section: Introductionmentioning
confidence: 99%
“…To cater to the demands of the large number of cores and to bridge the widening gap between the speed of processor core and DRAM memory, large sized shared LLCs (last level caches) are being used; for example, Intel's E7-8800 processor uses 24MB L3 cache. Further, with each CMOS technology generation, leakage power has been increasing dramatically [8,9]. Thus, power consumption of caches is increasingly becoming a concern in modern processor design.…”
Section: Motivation For Present Researchmentioning
confidence: 99%
“…With increasing number of cores integrated on a single chip [5,72], the pressure on the memory system is rising and to mitigate this pressure, modern processors are using large sized LLCs; for example, Intel's 32nm, 8-core Poulson processor uses 32MB of LLC [73]. Further, with each CMOS technology generation, leakage energy consumption has been increasing exponentially [8,9] and hence, large LLCs contribute significantly to the total processor power consumption [74]. The increased levels of power consumption necessitate expensive cooling solutions which significantly increase the overall system cost and design complexity and also restrict further performance scaling.…”
Section: Introductionmentioning
confidence: 99%